The Insult of Involuntary Adoption and the Moral Seriousness of MOTHERHOOD - Watson, Katie 19XX- (The Hastings Center report, 2025)
Adoption is often framed as an alternative to abortion. However, many women feel that pregnancy and birth made them a mother and that this new identity is not erased by the fact they are not raising that child. This article argues that involuntary adoption occurs when legislative coercion deprives a pregnant person of a realistic abortion option, forcing them into this position of being a parent who is not parenting. The article also argues that the moral seriousness of motherhood begins at conception, not because embryos are the moral equivalent of babies, but because that's when the pregnant person becomes a “potential mother” who must make a new set of decisions in response to her status. The reversal of Roe v. Wade has made narrative insight into the dynamics of pre-Roe adoption critical. Therefore, this article offers the stories of a 1969 birth mother's journey from being a teenager who relinquished her birth daughter to becoming a physician working in abortion care and of a 1965 adoptee's effort to reach out to her birthparents at age fifty-four as texts for ethical analysis.